2018
DOI: 10.1108/jic-03-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Improving corporate disclosure through XBRL

Abstract: Purpose The purpose of this paper is to examine the potential for eXtensible Business Reporting Language (XBRL) to go beyond static reporting. A taxonomy structure of information is developed for providing a knowledge base and insights for an XBRL taxonomy for integrated reporting (IR). Design/methodology/approach Design Science (DS) research, as a pragmatic exploratory research approach, is embraced to create a new “artefact” and thematic content analysis is used to analyse IR in practice. Findings Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Generally, IC studies divide the IC structure into three major elements: those of human capital, structural capital, and relational capital. However, some recent studies [29][30][31][32] have suggested other IC elements, such as social capital, spiritual capital, innovation capital, etc., which are more proper for a current business situation. Most IC structures still propose large IC elements that are quite extensive.…”
Section: Benchmarking Of Ic and Improvement Of The Ic Benchmarking Methodsmentioning
confidence: 99%
“…Generally, IC studies divide the IC structure into three major elements: those of human capital, structural capital, and relational capital. However, some recent studies [29][30][31][32] have suggested other IC elements, such as social capital, spiritual capital, innovation capital, etc., which are more proper for a current business situation. Most IC structures still propose large IC elements that are quite extensive.…”
Section: Benchmarking Of Ic and Improvement Of The Ic Benchmarking Methodsmentioning
confidence: 99%
“…With regard to the monologic approach, the increasingly important role played by the corporate websites in enhancing environmental communication, and the significance of supporting information "accessibility," started being evidenced more than 20 years ago (Jones et al, 1999). Still, nowadays, digital media plays an important role in effectively realizing intertextual connectivity because helping organizations' connection of relevant information, and therefore, facilitating users' website navigation (Brennan and Merkl-Davies, 2018;La Torre et al, 2018b). For instance, in their study, La Torre et al (2018b, p. 338) explore the role of XBRL (eXtensible Business Reporting Language) as a digital language for overcoming the "static and periodic reporting" toward a "more relevant and dynamic corporate disclosure for stakeholders" thus improving the International Integrated Reporting Council's connectivity principle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…annual results release), the unit of analysis (communication). It allowed as well to the definition of the logic process by means of which the cause-effect pattern of communication, occurring between the organization and its stakeholders, was put in relation and operationalized External validity Use of theory in single-case studies This paper focuses on the grand theory stating that NFD "needs to be mandatory to increase the accountability of undertakings within the EU" La Torre et al (2018aTorre et al ( , 2018b). The grand theory supporting the directive is re-examined: the exploration of the concept of "relational connectivity" Brennan and Merkl-Davies (2018) may help in the achievement of the directive's goal.…”
Section: Use Of Logic Modelsmentioning
confidence: 99%
“…As a result, XBRL, globally and especially in most developed countries, has gained tremendous popularity since its publication in early 2000. The benefits of using XBRL allow the company to electronically report its financial statements with guaranteed interoperability (Bonsón et al, 2009), accuracy (Troshani et al, 2015), and flexibility (Torre et al, 2018). Furthermore, by developing XML format, XBRL-based financial statements can be easily read by machine, or in this context is the internet.…”
Section: Introductionmentioning
confidence: 99%